Shades of Green Reporting: A Critical Discourse Analysis of Eco-News Reports in the Philippines - Philip Andrew L. Garlitos (Journal of Language and Literature, 2020)
This paper uncovers the ideological representations found in the linguistic patterns of eco-news reports of national and local dailies in the Philippines. By bringing the 25 mainstream news reports on environmental concerns to analysis using Faircloughs (1992) Critical Discourse Analysis Framework and Hallidays (1985) Systemic Functional Linguistics, findings reveal that the news reports serve to promote different core ideasaboutdestruction, allocation of blame, victimization, bias, risk and hazard, governments role, and objectification. Themes drawn out are found to represent nature astheenemy and the culprit of destruction, the government as the eco-warriors, the ordinary citizens as weak anddefencelessversus the authorities as empowered and influential, and plants and animals as human commodities. By way of turning verbs into nouns, active to passive structure, and subject to its metonymic representation, human involvement is concealed as social actors are removed in the text construction. Despite maintaining the objective nature of news reporting, the discourse is produced based ontheideological standpoints of the writers, which may feed readers understanding ofthe realities of nature and ecology as a whole.